It's not austerity. Or is it? Assessing the effect of austerity on growth in the European Union, 2010-15 - Fragetta, M.; Tamborini, R. (International Review of Economics and Finance, 2019)
We present a new econometric study of the effects of fiscal austerity on growth from 2010 to 2015 in a panel of the EU countries and the US as a proxy for the rest of the world, controlling for other conditioning factors put forward in the ”it's not austerity” view of the prolonged EU depression (low growth trend, loss of competitiveness, high sovereign debt and spread, excess taxation). Austerity remains significant with a negative effect in a range between 0.65 and 1.57 in the short run, and with spending cuts less harmful in the long run.